Pengaruh Profitabilitas, Hedging, dan Tingkat Utang terhadap Nilai Perusahaan Sub Sektor Batu Bara - Eggy Arrahman; Dewa Putra Krishna Mahardika (Jurnal Informatika Ekonomi Bisnis, 2023)
Firm value is the standard price of a company that is considered feasible for potential investors. Firm value helps investors in assessing the performance of a company and also how the company's prospects are. As the value of the company increases, it can lead to an increase in the level of shareholder welfare. The object used in this study is a coal sub-sector company listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The utilization of Indonesian coal continues to increase, both industrial needs and for the fulfillment of people's daily lives. A decrease in coal prices can affect the financial performance of coal companies and by affecting the value of the company. The purpose of this study is to determine the effect of profitability, hedging, and debt level on company value in coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2021 simultaneously and partially. This research uses data from the annual report and financial statements 2018-2021. The population in this study is coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2021. In sample selection, this study used purposive sampling and obtained 13 companies with a research period of 4 years, so that 52 units of research samples were obtained. The data analysis method used is panel data regression analysis. Based on the results of the study, profitability, hedging, and debt levels simultaneously affect the value of the company. Partially, profitability has a significant positive effect on the value of the company, while hedging and debt levels do not have a significant effect on the value of the company.